Enhanced oral bioavailability and hepatoprotective activity of thymoquinone in the form of phospholipidic nano-constructs. (1st February 2020) - Rathore, C.; Upadhyay, N.; Kaundal, R.; Dwivedi, R. P.; Rahatekar, S.; John, A.; Dua, K.; Tambuwala, Murtaza M.; Jain, S.; Chaudari, D.; Negi, P.
ABSTRACT: Background : The poor biopharmaceutical properties of thymoquinone (TQ) obstruct its development as a hepatoprotective agent. To surmount the delivery challenges of TQ, phospholipid nanoconstructs (PNCs) were constructed. Method : PNCs were constructed employing microemulsification technique and systematic optimization by three-factor three level Box-Behnken design. Result : Optimized PNC composition exhibited nano size (<100 nm), spherical morphology, within acceptable range of polydispersity index (0.55), high drug entrapment efficiency (>90%), controlled drug release pattern, and neutral surface charge (zeta potential of −0.65 mV). After oral administration of a single dose of PNC, it showed a relative bioavailability of 386.03% vis-à-vis plain TQ suspension. Further, TQ-loaded PNC demonstrated significant enhanced hepato-protective effect vis-à-vis pure TQ suspension and silymarin, as evidenced by reduction in the ALP, ALT, AST, bilirubin, and albumin level and ratified by histopathological analysis. Conclusion : TQ-loaded PNCs can be efficient nano-platforms for the management of hepatic disorders and promising drug delivery systems to enhance oral bioavailability of this hydrophobic molecule.